2016
DOI: 10.3329/baj.v19i1.29866
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sowing Time Based Temperature Variations on Growth, Yield and Seed Quality of Garden Pea

Abstract: A field experiment was conducted at the research field of Agronomy Division, BARI, Joydebpur, Gazipur and ARS, Burirhat, Rangpur to evaluate crop growth, yield and seed quality of garden pea in prevailing temperature at different sowing dates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
5
3
0
Order By: Relevance
“…The more pods per plant in 20th October sown crop is due to the fact that it gets more period for growth and development which consequently resulted in more pods per plant. Similar results were corroborated by Ali et al [ 22 ] in garden pea, as they reported that delay in sowing leads to a decrease in pods per plant as compared to timely sown crop.…”
Section: Discussionsupporting
confidence: 87%
“…The more pods per plant in 20th October sown crop is due to the fact that it gets more period for growth and development which consequently resulted in more pods per plant. Similar results were corroborated by Ali et al [ 22 ] in garden pea, as they reported that delay in sowing leads to a decrease in pods per plant as compared to timely sown crop.…”
Section: Discussionsupporting
confidence: 87%
“…In this context, Szczepanek and Olszewski (2009) showed that the delay of sowing resulted in reduction in chlorophyll content and the rate of photosynthesis and of leaves. These results are similar to that recorded by Ali et al (2016), El-Shafey et al . (2016 and Sumalatha and Uppar (2019).…”
Section: -Seed Quality: A-effect Of Sowing Datessupporting
confidence: 93%
“…The obtained results about planting dates are in agreement with Ali et al (2016) who indicated that the variation in growth duration of pea might be due to variation in day/night temperature and increased in temperature at the later sowing curtailed the crop growth duration. Similar results were recorded by Ezeakuet al (2015), Sirwaiya and Kushwah (2018) and Sumalatha and Uppar (2019).…”
Section: B-effect Of Foliar Applications and Vernalization Practicesupporting
confidence: 90%
“…2a and 2b and Fig.3a and 3b) that hastens forced maturity and reduced TDM production and translocation to the yield components. Similar results were recorded by Ali et al (2016). Weekly mean temperatures (max.…”
Section: Yield and Yield Attributessupporting
confidence: 88%
“…High-temperature stress affects reproductive development, as reported in legumes such as chickpea (Kaushal et al, 2013;Kumar et al, 2013) and pea (Guilioni et al, 1997). It was reported that different environmental conditions, especially temperature due to different sowing time provide variable in crop growth, development and yield stability (Ali et al, 2016). It is also needed to minimize the yield reduction by taking different management.…”
Section: Introductionmentioning
confidence: 99%